SYNCHRONOUS GENERATION OF TWO OSCILLATIONS OF MICROWAVE AND TERAHERTZ BANDS IN AVALANCHE GENERATOR DIODES WITH EXTERNAL SIGNAL - K. A. Lukin; P. P. Maksymov (Радиофизика и электроника, 2016)
Multifrequency avalanche-generator diodes (AGD) based on abrupt Si and GaAs p–n-junction from a high-alloy n-region were investigated. The time of realization of output power was calculated and a projection of the attractors in the 2D phase space of AGD was provided. The spectral analysis of output power was completed and electronic efficiency was defined. It is shown that the multi-frequency self-oscillations are excited synchronously in n- and p-regions of abrupt p–n-junction at higher harmonics of the external signal. The presented numerical results may be of interest to developers of powerful sources of electromagnetic waves of the microwave and terahertz range. The considered mode of synchronous generation of dual-frequency oscillations can be considered as the basis for the generation of so-called associated/confusing states of the electromagnetic field (Entangled Photons), i.e. the signals of different frequencies oscillating in time while phase ratios for different sensor and radar systems.